Influence of Supervisory Style on Supervision Outcomes among Undergraduate Trainee Counsellors - Nor Mazlina, Ghazali; Norashikin, Beddu; Azzahrah, Anuar; Edris, Aden; Wan Marzuki, Wan Jaafar; Fatahyah, Yahya (2021)
The research aimed to identify the influence of supervisory styles on supervision outcome among undergraduate trainee counsellors. This research was quantitative with correlational research design in order to identify the influence and relationship between independent and dependent variables among trainee counsellors. 100 respondents from two (2) public universities in Malaysia were recruited. Stratified random sampling technique was utilized to select the respondent and proportional stratification was used to determine the sample size of each stratum. Supervisory Styles Inventory (SSI) and Supervisory Satisfaction Questionnaire (SSQ) was the instrument used in this study. The System Approach to Supervision (SAS) Model become underlying theory in this research. The results of the study were analysed by using Pearson’s product-moment Coefficients and Multiple Regression. Based on the findings, the supervisory styles showed that there was significant relationship with supervision outcome (r= 0.49, p< 0.05). Three of supervisory styles which were attractive (r= 0.48, p< 0.05), interpersonally sensitive (r= 0.48, p< 0.05) and task-oriented (r= 0.42, p< 0.05). The supervisory styles also showed there was significant influence with supervision outcome. Among the three supervisory styles, attractive and interpersonally sensitive was the most influence on supervision outcome (R2=0.23, Adjusted R2=0.22, F(1, 98) = 29.05, p<0.05). The findings of this study perhaps could expand knowledge and understanding on the individual differences to supervision field. Supervisors could examine and reflect upon their styles based on theoretical framework provided and can restructure the styles. Lastly, it also can improve the quality and effectiveness of supervision for both supervisor and supervisee.